2019
DOI: 10.1590/1519-6984.182391
|View full text |Cite
|
Sign up to set email alerts
|

Quality of fresh and cryopreserved semen and their influence on the rates of fertilization, hatching and quality of the larvae of Piaractus mesopotamicus

Abstract: In this work, the seminal parameters of P. mesopotamicus were evaluated fresh and after cryopreservation, focusing on the sperm variables that affect the rates of fertilization, hatching and post-hatching parameters such as larval survival and morphology. The semen and oocytes from the animals were collected after extrusion, and seminal quality and oocyte fertilization were analyzed. Subsequently, a portion of each semen sample was cryopreserved and, after two days, the oocytes from three new females were fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
1
13
0
6
Order By: Relevance
“…It has been confirmed that the freezing process can cause injuries to both head and tail of sperm (Galo et al, 2019). CPAs' toxicity and temperature reduction are responsible for such sperm abnormalities.…”
Section: Discussionmentioning
confidence: 95%
“…It has been confirmed that the freezing process can cause injuries to both head and tail of sperm (Galo et al, 2019). CPAs' toxicity and temperature reduction are responsible for such sperm abnormalities.…”
Section: Discussionmentioning
confidence: 95%
“…However, effects of cryopreservation could have been confounded with effects of intracytoplasmic sperm injection in their study. In fish, no effect of sperm cryopreservation on offspring performance could be found in some species [24][25][26][27][28][29], while significant effects on several developmental traits were reported in others [30][31][32][33]. In the latter case, effects of cryopreservation on potential indicators of offspring fitness were sometimes negative [30,31] and sometimes positive [32], and sometimes results were mixed [33].…”
Section: Introductionmentioning
confidence: 94%
“…The removal of two of the studies (Galo et al, 2011; Streit et al, 2009) decreased the MD to −2.52% and −2.65% respectively. The removal of another study (Galo et al, 2019) increased the combined estimate, leaving the MD = −1.28%. For the percentage of cells with secondary abnormalities, the sensitivity analysis showed that the removal of three studies (Da Costa et al, 2019; Galo et al, 2011, 2019) increased the MD by 0.26% to 0.81, 0.46 and −0.32 respectively.…”
Section: Resultsmentioning
confidence: 95%
“…The removal of another study (Galo et al, 2019) increased the combined estimate, leaving the MD = −1.28%. For the percentage of cells with secondary abnormalities, the sensitivity analysis showed that the removal of three studies (Da Costa et al, 2019; Galo et al, 2011, 2019) increased the MD by 0.26% to 0.81, 0.46 and −0.32 respectively. On the other hand, the removal of the study by Streit et al (2009) decreased the combined estimate (MD = −0.15).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation